Attitudes and Perceptions of Newspaper Journalists Towards Public Relations Practitioners in New Zealand - Callard, Hayley (Auckland University of Technology, 2011)
This study examines the attitudes and perceptions newspaper journalists hold towards public relations (PR) practitioners in New Zealand and why such attitudes exist. To date, only two academic studies in New Zealand have explored the topic. This study updates and expands on knowledge that exists overseas and in New Zealand. A combination of data collection methodologies were used for this study, comprising an online, predominantly quantitative, survey and a series of eight semi-structured interviews with working newspaper journalists. Thematic content analysis was used to analyse and interpret qualitative data. The findings show that the attitudes newspaper journalists hold towards PR practitioners in New Zealand are generally negative and complex. Such attitudes are borne out of frustrations arising from some of the media relations tactics employed by PR practitioners, as well as the oppositional nature of two industries, and economic pressures of the newsroom. These frustrations, particularly the latter two, challenge a journalist’s ability to uphold traditional journalistic values. This study also found evidence of some warming in the attitudes New Zealand newspaper journalists have towards PR practitioners. This is restricted predominantly to perceptions about unethical behaviour, status and toeing an organisational line, all of which point to a downward shift in the level of hypocrisy journalists have long been accused of holding when it comes to PR practitioners. Furthermore, it is apparent that journalists’ attitudes vary according to the sector and even the organisation in which a PR practitioner works, highlighting the view that consumer PR, in particular, is poorly regarded by newspaper journalists in New Zealand. This study acts as a useful resource to PR practitioners and the wider PR industry by highlighting where and how PR practitioners have the ability to improve interactions to create more harmonious, beneficial relationships.
Keywords: Journalism; Public relations; Media; Newspapers